2018
DOI: 10.1108/sgpe-d-17-00029
|View full text |Cite
|
Sign up to set email alerts
|

Seeking “better ways”: early career faculty researcher development

Abstract: Purpose Researcher development is an important but underexplored topic with implications for knowledge production, graduate education, faculty development and equity in higher education. The purpose of this constructivist instrumental case study was to understand how the process of writing and publishing from qualitative dissertations sparked researcher development among two pre-tenure faculty members in higher education. Design/methodology/approach Two researchers and seven data sources (i.e. six essays and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The demand to work collaboratively was also identified by these ECRs as challenging in the absence of a clear researcher identity, as they were unsure to which 'tribe' they should or could connect. Robbins et al (2018) reported similar challenges for ECRs where there were not ready-made collaborations in place postdoctorate. As Drew explained, "You don't know where you fit but you are being told that you must fit!".…”
Section: Persistent Liminalitymentioning
confidence: 93%
“…The demand to work collaboratively was also identified by these ECRs as challenging in the absence of a clear researcher identity, as they were unsure to which 'tribe' they should or could connect. Robbins et al (2018) reported similar challenges for ECRs where there were not ready-made collaborations in place postdoctorate. As Drew explained, "You don't know where you fit but you are being told that you must fit!".…”
Section: Persistent Liminalitymentioning
confidence: 93%
“…Within the discussion of outcomes of agency, the impact of both our internal and external interpretations on our actions and perceptions align with other examples from faculty research. For instance, research focused on early career faculty reinforces the importance of external interpretations, such as peer reviews within the journal publication process, as faculty attempt to pursue impact within their fields (e.g., Robbins & LePeau, 2018). As another example, in a study of race-related service and agency, Baez illustrates an important dynamic between faculty members exercising agency to participate in race-related service and the external assessment of service within the "traditional notions of merit" (2000, p. 389).…”
Section: Connecting the Theory Components To Existing Agency Frameworkmentioning
confidence: 99%
“…Faculty and administrator pipeline programs assist their participants with the iterative process of learning coping skills during times of rejection, accepting constructive criticism, building mentoring networks, and developing academic socialization skills (Robbins & LePeau, 2018). In this section, we will illustrate some of the hallmark URM faculty and postdoctoral programs (the University of California President's Postdoctoral Fellowship Program, the National Center for Faculty Development & Diversity (NCFDD) Faculty Success Program, the Sisters of the Academy [SOTA] Institute, the Rochester Institution of Technology [RIT] Future Faculty Career Exploration Program, and the Creating Connections Consortium [C3]), which have assisted many underrepresented minority (URM) postdoctoral researchers and faculty members to move successfully through their academic life journey.…”
Section: Aera Minority Dissertation Fellowship Program In Educationmentioning
confidence: 99%